Does the world need faunists? Based on rotifer (Rotifera) occurrence reflections on the role of faunistic research in ecology. Issue 3 (6th May 2019) - Ejsmont‐Karabin, Jolanta
Abstract: Most faunistic studies of large‐scale patterns concern terrestrial vertebrates, whereas smaller organisms, and in particular, freshwater invertebrates like rotifers receive less attention. As a result, the "rotiferologists" effect", that is sampling intensity, is among the most influential factors observed, globally or locally, on species richness. Because there are many more small, isolated patches of habitats available to the specialist species, greater specialization has occurred in those forms than in ubiquitous species. This rule also applies to rotifers. Results show that: (a) the total number of rotifer species observed in a lake depends on both the number of samples collected and the type and number of lake habitats involved; and (b) the originality (variability) of rotifer fauna in particular lakes is more pronounced with the more species found in a lake. The important purpose of faunistic studies is the registration of indigenous species. The inflow of alien species is currently one of the greatest threats to the preservation of natural fauna. However, if we do not recognize the composition of natural communities, we will not be able to recognize the invaders. The second most important goal is to enable tracking of long‐term changes in species diversity of rotifer fauna. Rotifers seem to be sensitive enough to climate change and pollution of the aquatic environment. Thus, for the reasons described above, faunistics will be still necessary.